Pedagogical Technology in Fine Art Education - Rahimova Madina Yashnarjon qizi, (European Journal of Life Safety and Stability (2660-9630), 2024)
In this article, the issue of pedagogical technology in the teaching of visual arts at school, as well as the issue of creating methodical and didactic manuals, is studied more broadly, technology, pedagogical technology, and then pedagogical technologies in the teaching of visual arts we found it necessary to analyze the issue of use.